Interaction between behavioral inhibition and neural alcohol cue-reactivity in ADHD and alcohol use disorder - Vollstädt-Klein, Sabine; Gerhardt, Sarah; Lee, A.; Strosche, A.; Sharafi, Georg Friedrich; Nuriyeva, R.; Seidt, J.; Hennig, O.; Alm, B.; Hermann, Derik; Sommer, Wolfgang H.; Kiefer, Falk; et al. (Psychopharmacology, 2020)
Compared to the general population, adult Attention-Deficit / Hyperactivity Disorder (ADHD) is more prevalent in patients with Alcohol Use Disorder (AUD). Impaired behavioral inhibition is a common characteristic in both ADHD and AUD. Relapse risk is increased in patients with AUD and comorbid, untreated ADHD and in AUD patients with increased neural cue-reactivity.
Gesehen am 07.12.2021